Strategi Pemerintah Daerah dalam Pemberdayaan UMKM guna Meningkatkan Daya Saing Sektor Perdagangan dan Industri (Studi Di Dinas Perindagkoppar dan UMKM Kota Madiun) - Suhartini, Hidayati (Jurnal Administrasi Publik, 2015)
Abstract: Local Goverment strategies for UMKM Empowerment to Increase The Competing Ability of Trade and Industrial Sectors (Study at PERINDAGKOPPAR of Madiun City. Most industries in Madiun City are high-cost production such that they cannot compete in price basis against import products with more comparative values over local product. Therefore, local goverment strategies for the empowerment of micro, small, medium enterprises (MSME) are truly important to increase the competing ability of trade and industrial sectors in Madiun City. Result of research reveals that local government strategies for MSME (micro, small and medium enterprises) empowerment to increase the competing ability of trade and industrial sectors in Madiun City are by increasing the capitalization, developing the markets for MSME (micro, small and medium enterprises), improving the quality of human resource, and improving the quality of technology. Main determinant indicators for these strategies are effectiveness,efficiency and innovativeness. Keywords: Strategy, MSME (micro, small and medium enterprises) Empowerment, Competing Ability, Trade and Industrial Sector. Abstrak: Strategi Pemerintah Daerah dalam Pemberdayaan UMKM guna Meningkatkan Daya Saing Sektor Perdagangan dan Industri (Studi di Dinas PERINDAGKOPPAR Kota Madiun). Industri-industri di Kota Madiun pada umumnya menggunakan pola produksi biaya tinggi (high cost production) sehingga kurang mampu bersaing di dalam harga dengan produk-produk import yang bisa memberikan nilai perbandingan lebih daripada produk lokal. Oleh karena itu, diperlukannya strategi pemerintah daerah untuk meningkatkan daya saing sektor perdagangan dan industri yang ada di Kota Madiun melalui pemberdayaan UMKM. Hasil penelitian ini mengungkapkan bahwa strategi yang dilakukan oleh pemerintah daerah yaitu dengan cara peningkatan permodalan, pengembangan pasar UMKM, peningkatan kualitas SDM, dan peningkatan kualitas teknologi. Indikator utama penentu strategi tersebut yaitu efektifitas, efisiensi, dan inovatif. Kata Kunci: Strategi, pemberdayaan UMKM, daya saing, sektor perdagangan dan industri